PERCEIVED EFFECTIVENESS OF FRAUD DETECTION AUDIT PROCEDURES IN GOODS AND SERVICES EXPENDITURES - Hendra Dwi Saputra Sumarseno; Anis Chariri (Diponegoro Journal of Accounting, 2015)
The aims of this research is to examine the perceptions of auditors about the effectiveness of standard audit procedures in detecting fraud in goods and services expenditures.            The population of this study is BPK RI’s auditors in AKN I, AKN II, AKN III, AKN IV, AKN V, and AKN VI. Research sample obtained in this study is 34 auditors. Respondents were given a questionnaire and asked to respond within five Likert scale. Data were analyzed using one-sample t-test and independent sample t-test.            The result showed that there are some standard audit procedures in goods and services expenditures that are perceived as more effective and others are perceived as moderately effective. It is found that there are no significant differences in the perceiving the effectiveness of standard audit procedures between less experienced auditor and more experienced auditor. The study has also found that there are only one procedure that has significant difference in the perceived effectiveness of standard audit procedure between male auditor and female auditor.